Forest reforestation strategy in the remaining tree mining area in Aceh, Indonesia - Ahmad Zamroni (P2M Politeknik Pertanian Negeri Samarinda, 2019)
Almost half the forest area (49 percent) is relatively intact, while 9 percent is found in fragments with little or no connectivity. Tropical rainforests and boreal coniferous forests are the least fragmented, whereas subtropical dry forest and temperate oceanic forests are among the most fragmented. Roughly 80 percent of the world’s forest area is found in patches larger than 1 million hectares. The remaining 20 percent is located in more than 34 million patches across the world – the vast majority less than 1 000 hectares in size.